2020
DOI: 10.3390/ijms21072604
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-Derived Pyridinium Evokes Renal Tubular Cell Damage via RAGE Interaction

Abstract: Glyceraldehyde-derived advanced glycation end products (glycer-AGEs) contribute to proximal tubulopathy in diabetes. However, what glycer-AGE structure could evoke tubular cell damage remains unknown. We first examined if deleterious effects of glycer-AGEs on reactive oxygen species (ROS) generation in proximal tubular cells were blocked by DNA-aptamer that could bind to glyceraldehyde-derived pyridinium (GLAP) (GLAP-aptamer), and then investigated whether and how GLAP caused proximal tubular cell injury. GLAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nevertheless, our study agrees with previous studies demonstrating that AGE accumulation is a predictor of all-cause mortality in CKD [ 34 , 35 ]. Although AGE are mainly considered promoters of glomerular lesion, in vitro and pre-clinical studies suggested a potential role also in tubular injury [ 36 , 37 , 38 , 39 ], but no human studies have explored this issue yet. Therefore, additional studies exploring the associations between AGE and tubular injury markers could be helpful in identifying additional tools for disease monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our study agrees with previous studies demonstrating that AGE accumulation is a predictor of all-cause mortality in CKD [ 34 , 35 ]. Although AGE are mainly considered promoters of glomerular lesion, in vitro and pre-clinical studies suggested a potential role also in tubular injury [ 36 , 37 , 38 , 39 ], but no human studies have explored this issue yet. Therefore, additional studies exploring the associations between AGE and tubular injury markers could be helpful in identifying additional tools for disease monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs cause tubular damage that progress to DKD. Excess AGEs content leads to oxidative stress [6], inflammation [7], or apoptosis [8] in renal tubules. In the previous study, we had shown the role of AGEs in inducing cholesterol production that is mediated by 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCoAR) and cholesterol absorption mediated by low-density lipoprotein receptor (LDLr) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that AGEs play important roles in tubular injury during DKD. Excessive levels of AGEs can cause renal tubular oxidative stress [6], inflammatory responses [7], and even apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%